2018
DOI: 10.1155/2018/8170436
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB-94ins/del ATTG Genotype Contributes to the Susceptibility and Imbalanced Th17 Cells in Patients with Immune Thrombocytopenia

Abstract: Background The NLRP3 inflammasome plays important roles in the pathogenesis of autoimmune diseases. However, the role of the NLRP3 inflammasome in the pathophysiology of immune thrombocytopenia (ITP) remains unclear. Methods RT-PCR was used to examine the polymorphism and expression of genes involved in the NLRP3 inflammasome in ITP patients. T helper cells and apoptosis of PBMC from ITP patients were analyzed by flow cytometry. The antiplatelet autoantibodies in plasma were determined by modified monoclonal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Given the importance of these cytokine dysregulation, some Authors focused on Treg/Th17 imbalance and on cytokine genes polymorphisms. In a recent study, it has been shown that NF-κB-94ins/del ATTG genotype (involved in the NLRP3 inflammasome) contributes to ITP development and to imbalanced Th17 cell response (119). Another study on IL-17F rs763780 polymorphism, that has been associated with IL-17 expression and activity, showed a lower prevalence in ITP cases (N = 165) compared to healthy controls (118).…”
Section: Studies On Cell-mediated Immunitymentioning
confidence: 99%
“…Given the importance of these cytokine dysregulation, some Authors focused on Treg/Th17 imbalance and on cytokine genes polymorphisms. In a recent study, it has been shown that NF-κB-94ins/del ATTG genotype (involved in the NLRP3 inflammasome) contributes to ITP development and to imbalanced Th17 cell response (119). Another study on IL-17F rs763780 polymorphism, that has been associated with IL-17 expression and activity, showed a lower prevalence in ITP cases (N = 165) compared to healthy controls (118).…”
Section: Studies On Cell-mediated Immunitymentioning
confidence: 99%
“…Therefore, the antiplatelet autoantibody is a major causative factor for the pathogenetic mechanism of ITP [ 1 4 ]. Antiplatelet autoantibodies mediate platelet destruction by binding to platelet membrane glycoproteins (GPs), including GPIIb/IIIa, GPIb/IX, and GPIV, and impair or inhibit platelet production by megakaryocytes by specifically recognizing platelet antigens located on megakaryocytes (such as GPIb and GPIIb/IIIa) [ 3 7 ]. In our study, 40% of ITP patients had positive antiplatelet autoantibodies as well as low platelet counts in comparison with patients with negative antiplatelet autoantibodies, indicating that antiplatelet autoantibodies might aggravate platelet destruction and impair platelet production that causes reduced peripheral platelet counts.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-four sex- and age-matched healthy controls (HCs) were recruited from the Healthy Management Center of the First Affiliated Hospital, Zhejiang University School of Medicine. All ITP patients were diagnosed according to consensus guidelines, and the patients and HCs who had cardiovascular disease, diabetes, pregnancy, obesity, infections, or connective tissue diseases were excluded from our study [ 3 ]. The median age of patients at the onset of primary ITP and the median age of the HCs were 37 (range, 19-66) and 37 years old (range, 20-68), respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also abundant evidence that NF-κB is necessary for maintaining immune tolerance due to its actions during thymic selection, both for negative selection of autoreactive T cells and selection and maintenance of Tregs [ 14 ]. Yu et al reported that increased activation of NF-κB may promote the development of ITP by the NOD-like receptor pyrin domain-containing protein 3 (NLRP3) inflammasome [ 15 ].…”
Section: Introductionmentioning
confidence: 99%